Bipolar radiofrequency thermotherapy vs. transurethral resection of the prostate: Effect on nocturia as a result of benign prostatic obstruction - Yuce, Ahmet; Benli, Erdal; Cirakoglu, Abdullah; Yazici, Ibrahim; Nalbant, Ismail (Canadian Urological Association Journal, 2022)
Introduction: The purpose of this study was to investigate and compare the effects of radiofrequency thermotherapy (RF) thermotherapy and transurethral resection of the prostate (TURP) on nocturia and associated quality of life in patients diagnosed with benign prostatic obstruction (BPO) under medical treatment who have complaints of persistent nocturia. Methods: The results of patients who underwent RF thermotherapy and TURP procedures between February 2019 and February 2022 were examined, and their three-month results were compared based on their uroflowmetry values, International Prostate Symptom Score (IPSS) values, nocturia frequency, and Nocturia Quality of Life Questionnaire scores. Results: While the frequency of nocturia in the RF thermotherapy group that was 4.5±1.6 before the procedure decreased to 2.3±1.4 after the procedure (p=0.002), this value in the TURP group decreased from 5.1±2.42 to 3.9±2.1 (p=0.044). RF thermotherapy was found to be more effective than TURP (p<0.005). Significantly, more noticeable improvements were observed in most nocturia-related next-day complaints and nocturia-related concerns in the RF thermotherapy group than the TURP group. Conclusions: It was observed that RF thermotherapy had a more acceptable effect on obstructive complaints in comparison to TURP, and it could be more effective on nocturia and associated quality of life. RF ablation treatment may be offered as an appropriate option to treat nocturia complaints in suitable patients.